Olefin polymerization catalyst system as well as preparation method and application thereof

By using metal composite components of tetraacylsaccharide phenylsilane compounds and ultrafine inorganic oxide support in the olefin polymerization catalyst, the problem of high hexane extractable content in the existing catalyst is solved, and a catalyst system with high activity and low oligomer content is achieved.

CN119552284APending Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311130783.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing olefin polymerization catalyst has a high content of hexane extract in polymer powders produced by homopolymerization of ethylene, affecting industrial production.

Method used

The metal composite components containing tetraacylphenylsilane compounds are used to combine with ultrafine inorganic oxide support to form a highly active catalyst system to improve the activity and dispersion of the catalyst.

Benefits of technology

The hexane extractable content in the polymer powder is significantly reduced, the activity of the catalyst and the melt index of the polymer are improved, and the oligomer content is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004430083920000101
    Figure BDA0004430083920000101
Patent Text Reader

Abstract

The invention relates to the field of olefin polymerization catalysts, and discloses an olefin polymerization catalyst system as well as a preparation method and application thereof. The olefin polymerization catalyst system comprises an organic aluminum compound and a metal composite component containing an acyl phenyl group, and the metal composite component containing the acyl phenyl group comprises a mixture of a tetraacyl phenyl silane compound, magnesium halide, titanium halide, an oxygen-containing organic compound and an ultrafine inorganic oxide and / or a reaction product of the components. The acyl phenyl group and the metal component in the catalyst system enable the obtained catalyst to have higher activity, and in addition, the superfine inorganic oxide carrier added in the catalyst component enables the catalyst to have better dispersity and more excellent catalytic effect. The polymer prepared by adopting the catalyst has high melt index and low oligomer content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of olefin polymerization catalysts, and in particular relates to an olefin polymerization catalyst system and a preparation method and application thereof. Background Art

[0002] Catalyst systems containing Ti / Mg complexes are commonly used in the polyolefin industry. The main catalyst used in the early production of polyethylene by Univation's UNIPOL process unit was the M-1 catalyst (UCAT-A) with silica gel as the carrier. Because silica gel is used as the carrier, the fluidity and mechanical strength of the catalyst are high, and the direct application in the gas phase fluidized bed has a better effect, and the particle properties of the polymer can be controlled to a certain extent. However, with continuous production practice, the M-1 titanium catalyst shows that the stability of solid feeding is difficult to ensure, and the catalyst system is prone to blockage and bridging. At the same time, the catalyst is highly sensitive to electrostatics caused by impurities in the reaction system, causing reactor flakes and agglomerations; and the M-1 catalyst is less efficient, and its resin product has a high ash content, resulting in a high catalyst cost per unit product and affecting the quality of the film product. The J-type catalyst was developed to overcome the shortcomings of the M-1 catalyst. The main components of the J-type catalyst are basically the same as those of the M-1 catalyst, but there are obvious differences in the preparation process. The J-type slurry polyethylene catalyst uses slurry feeding to overcome the shortcomings of difficult to control the addition amount, difficult to feed at a uniform speed, and static electricity during solid feeding. Moreover, due to the use of finer silica gel and higher tetrahydrofuran content than the M-1 type catalyst, the activity of the catalyst is increased by 3 to 4 times.

[0003] In the homopolymerization of ethylene or the copolymerization of ethylene and α-olefins, the performance of the catalyst affects the performance of the polymer. While catalyzing the polymerization of ethylene, the catalyst will produce some oligomers, which change the stress conditions between polyethylene molecules, affecting the performance and processing properties of the product, and affecting the yield strength, elongation and rigidity of the product. The amount of oligomers is generally measured by the amount of hexane extracts, so the amount of hexane extracts is also an important indicator for measuring catalyst performance.

[0004] Chinese patent CN101962417A provides a solid catalyst component for ethylene polymerization and a preparation method thereof, which is obtained by the following three consecutive synthesis steps: in the presence of halogen or a compound containing halogen elements, using magnesium and alcohol to prepare a magnesium-containing solid; then using an organic metal compound or a mixture of an organic metal compound and an electron donor to treat the magnesium-containing solid to obtain a magnesium-containing catalyst carrier; in the presence of an inert diluent, using a transition metal titanium compound to treat the magnesium-containing catalyst carrier to obtain a catalyst component. It has the characteristics of simple process, easy operation, low investment in industrial equipment, low production cost and easy control of product quality. Catalyzing ethylene polymerization together with alkyl aluminum has the characteristics of high catalyst activity and bulk density, less subdivision of generated polyethylene powder, etc., suitable for slurry polymerization or gas phase polymerization of ethylene, especially suitable for gas phase fluidized bed polymerization process of ethylene where the catalyst is fed in the form of slurry. The catalyst of the present invention has high activity, higher bulk density of the obtained polymer, and higher melt index. However, the catalyst prepared by this scheme has a high content of hexane extractables in the polymer powder generated by ethylene homopolymerization, which has an adverse effect on industrial production.

[0005] Chinese patent CN101376680A discloses a catalyst component for ethylene polymerization or copolymerization, a preparation method thereof, and the application of a catalyst composed of the catalyst component in ethylene polymerization or copolymerization. The catalyst component is a solid material containing magnesium / titanium, on which at least one inorganic titanium compound, at least one organic titanium compound, at least one electron donor, and at least one activator are loaded. The invention provides a solid catalyst component that is efficient, highly hydrogen-adjustable, and can produce a polymer with a low fine powder content, has a relatively narrow particle size distribution and a small average particle size, has a high catalyst activity, is suitable for slurry polymerization or gas phase polymerization of ethylene, and is particularly suitable for a gas phase fluidized bed polymerization process of ethylene in which the catalyst is fed in the form of a slurry. However, industrial tests have shown that the catalyst is not very suitable for a high-load, high-condensation rate fluidized bed production process, and is prone to powder stickiness. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a metal composite component containing a tetraacylphenylsilane compound, and uses the metal composite component in a catalyst system for olefin polymerization. The catalyst system provided by the present invention contains a metal component and an acylphenyl functional group, so that the obtained catalyst has higher activity. In addition, the ultrafine inorganic oxide carrier added to the catalyst component has good dispersibility in the catalyst system, so that the catalytic effect of the catalyst is more excellent.

[0007] One of the purposes of the present invention is to provide an olefin polymerization catalyst system, comprising: an organic aluminum compound, a metal composite component containing acylphenyl, wherein the metal composite component containing acylphenyl comprises a mixture of tetraacylphenylsilane compounds, magnesium halide, titanium halide, oxygen-containing organic compounds, ultrafine inorganic oxides and / or reaction products of the above components.

[0008] According to the present invention, in the olefin polymerization catalyst system, the molar ratio of the aluminum element in the organic aluminum compound to the titanium element in the metal composite component containing acylphenyl is (5-350):1, preferably (15-180):1.

[0009] According to the present invention, in the metal composite component containing acylphenyl groups:

[0010] In the metal composite component, the content of titanium is 0.2-5.0wt%, for example, it can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5wt%, or a value or a range of values ​​between any two of the above values; preferably, the content of tantalum is 0.8-4.0wt%, more preferably 1.5-2.5wt%;

[0011] Based on 1 mol of the titanium halide, the amount of the magnesium halide is 0.5 to 15 mol, preferably 1 to 10 mol, more preferably 2 to 8 mol; the amount of the tetraacylphenylsilane compound is 0.02 to 12 mol, preferably 0.05 to 8 mol, more preferably 0.1 to 4.5 mol; the amount of the oxygen-containing organic compound is 1 to 450 mol, preferably 30 to 250 mol, more preferably 120 to 200 mol;

[0012] In the metal composite component containing acylphenyl groups, the content of the ultrafine inorganic oxide is 5 to 45 wt %, preferably 8 to 35 wt %, and more preferably 15 to 30 wt %.

[0013] According to the present invention, in the olefin polymerization catalyst system:

[0014] The ultrafine inorganic oxide is selected from at least one of alumina and silicon dioxide, preferably silicon dioxide; the particle size of the ultrafine inorganic oxide is 0.005 to 10 μm, preferably 0.01 to 5 μm, more preferably 0.01 to 1 μm;

[0015] The general formula of the organoaluminum compound is AlR n X 3-n, wherein R is a C1-C20 straight chain or branched hydrocarbon group, preferably a C1-C10 straight chain or branched hydrocarbon group; X is a halogen, preferably chlorine; 0<n≤3; specifically, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride;

[0016] The general formula of the tetraacylphenylsilane compound is (R'Ph)4Si, wherein R' is selected from at least one of C1-C8 acyl or alkyl acyl groups, preferably at least one of C1-C3 acyl or alkyl acyl groups; specifically, the tetraacylphenylsilane compound is selected from at least one of tetrakis(4-formylphenyl)silane and tetrakis(4-acetylphenyl)silane;

[0017] The magnesium halide may be a commonly used magnesium halide compound, for example, the magnesium halide is selected from at least one of magnesium chloride, magnesium bromide, and magnesium iodide;

[0018] The titanium halide may be a commonly used titanium halide compound, for example, the titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide, and titanium tetrabromide, preferably at least one of titanium trichloride and titanium tetrachloride;

[0019] The oxygen-containing organic compound is selected from at least one of esters, ethers, and ketones, preferably at least one of alkyl esters of C1-C8 saturated fatty carboxylic acids, alkyl esters of C7-C8 aromatic carboxylic acids, C2-C8 fatty ethers, C3-C8 cyclic ethers, and C3-C10 saturated fatty ketones; specifically, the oxygen-containing organic compound is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, preferably at least one of methyl formate, ethyl acetate, n-butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, more preferably tetrahydrofuran.

[0020] The second object of the present invention is to provide a method for preparing the above-mentioned olefin polymerization catalyst system, comprising: mixing components including the organic aluminum compound and the metal composite component containing acylphenyl to obtain the olefin polymerization catalyst system.

[0021] According to the present invention, the method for preparing the metal composite component containing acylphenyl comprises:

[0022] (1) reacting components including a tetraacylphenylsilane compound, a magnesium halide, a titanium halide, and an oxygen-containing organic compound to obtain a mother liquor;

[0023] (2) Adding ultrafine inorganic oxide to the mother liquor obtained in step (1) to obtain a slurry, and spray drying to obtain the catalyst system.

[0024] According to the present invention, in the method for preparing the metal composite component containing acylphenyl groups:

[0025] In the step (1), the reaction conditions are: reaction temperature is 60-85°C, and reaction time is 2-4h;

[0026] In the step (2), the ultrafine inorganic oxide can be used in a solid form or in a dispersed liquid form, such as commercially available silica gel;

[0027] In the step (2), spray drying can adopt the spray drying equipment and drying process conditions commonly used in the art. Preferably, the spray drying conditions include: an inlet temperature of 100-240°C, preferably 120-200°C; an outlet temperature of 60-110°C, preferably 100-110°C.

[0028] A third object of the present invention is to provide an application of the above-mentioned olefin polymerization catalyst system or the olefin polymerization catalyst system obtained by the above-mentioned preparation method in olefin polymerization reactions.

[0029] According to the present invention, the olefin polymerization catalyst system is added to a polymerization reaction system containing a hydrocarbon organic solvent, the catalyst is activated in the hydrocarbon organic solvent, and then the olefin polymerization reaction is initiated. The hydrocarbon solvent includes but is not limited to isopentane, hexane, heptane, toluene, xylene, naphtha, mineral oil, etc.

[0030] In order to make the solid catalyst component obtained after spray drying suitable for the production of ethylene polymers, an activator component (e.g., an organic aluminum compound) is required to reduce the titanium atoms in the catalyst component to a state that allows ethylene to be effectively polymerized. Generally, the above-mentioned catalyst component and the activator component are reacted in a hydrocarbon solvent to obtain a catalyst capable of catalyzing olefin polymerization; the above-mentioned catalyst component and the activator component can also be added to the reaction system during the polymerization process and reacted in a hydrocarbon organic solvent to initiate olefin polymerization.

[0031] The catalyst of the present invention is suitable for homopolymerization of various ethylenes or copolymerization of ethylene and alpha-olefins, wherein the alpha-olefin can be selected from one of propylene, butene, pentene, hexene, octene and 4-methylpentene-1. The polymerization process can adopt gas phase method, slurry method and solution method, and is more suitable for gas phase fluidized bed polymerization. The conditions for olefin polymerization can be conventionally selected according to the prior art, and will not be described in detail here.

[0032] The multiple phenyl groups in the tetraacylphenylsilane compounds used in the present invention have a strong electron-donating effect, so that the silicon atoms therein can effectively improve the polymerization efficiency of the active center of the catalyst after coordination with the active center, and then a highly active catalyst is obtained after activation under the action of an organic aluminum compound. The polymer prepared by using the catalyst has a higher melt index, low hexane extract and low oligomer content. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0034] The test instruments and test conditions used in the examples are as follows:

[0035] 1. Catalyst activity: expressed as the weight of polymer obtained per gram of catalyst;

[0036] 2. Polymer melt index (MI): 6932 melt index tester, CEAST, Italy;

[0037] 3. Hexane extractable content in polymer powder (wt%): The dried polymer powder is extracted with hexane, specifically, the polymer is eluted with hexane for 4 hours. The percentage of the weight difference of the polymer powder before and after extraction to the weight of the polymer powder before extraction is the hexane extractable content in the polymer powder;

[0038] 4. Determination of titanium content in catalyst components: Dissolve the catalyst sample with 1M sulfuric acid, measure the dissolved solution with a spectrophotometer, and calculate the titanium content using the working curve;

[0039] 5. The content of inorganic oxide is obtained by calculating the ratio of feed amount to output catalyst mass.

[0040] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0041] Example 1

[0042] (1) Preparation of catalyst system

[0043] Into a 250mL three-necked flask purged with nitrogen, 2.25g TiCl4, 6.0g anhydrous MgCl2, 4.5g tetrakis(4-formylphenyl)silane and 150mL tetrahydrofuran were added successively, the temperature was raised to 65°C with stirring, the reaction was carried out at this temperature for 3 hours, and the temperature was lowered to 35°C to obtain a mother liquor.

[0044] Into a 250mL three-necked flask purged with nitrogen, 9 grams of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1 μm) was added, and the cooled mother liquor was added, the temperature was maintained at 35°C, and after stirring for 1 hour, the mother liquor mixed with silica gel was spray dried using a spray dryer. The spraying conditions were: inlet temperature 195°C, outlet temperature 110°C, to obtain a catalyst system with a titanium content of 2.22wt% and a silica content of 23wt%.

[0045] (2) Ethylene slurry polymerization

[0046] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, and 4mL of 1M triethylaluminum / hexane and 0.02g of the above-obtained catalyst system were added at the same time, the temperature was raised to 75°C, 0.18Mpa of hydrogen was added, and after the hydrogenation was completed, 0.75Mpa of ethylene was added, the temperature was raised to 85°C, and after reacting for 2 hours, the temperature was lowered and the material was discharged. The polymerization results are shown in Table 1.

[0047] Example 2

[0048] (1) Preparation of catalyst system

[0049] The same as Example 1, except that the reaction temperature was adjusted to 85° C., the reaction time was adjusted to 4 hours, and the titanium content of the obtained catalyst component was 2.30 wt %, and the silicon dioxide content was 22 wt %.

[0050] (2) Ethylene slurry polymerization

[0051] Same as Example 1, the polymerization results are shown in Table 1.

[0052] Example 3

[0053] (1) Preparation of catalyst system

[0054] The same as Example 1, except that the spray inlet temperature was adjusted to 170°C, the outlet temperature was 100°C, and the titanium content of the obtained catalyst component was 2.09wt%, and the silicon dioxide content was 21wt%.

[0055] (2) Ethylene slurry polymerization

[0056] Same as Example 1, the polymerization results are shown in Table 1.

[0057] Example 4

[0058] (1) Preparation of catalyst system

[0059] The same as Example 1, except that the amount of tetrakis(4-formylphenyl)silane used is 9.0 g, and the titanium content of the obtained catalyst component is 2.28 wt%, and the silicon dioxide content is 22 wt%.

[0060] (2) Ethylene slurry polymerization

[0061] Same as Example 1, the polymerization results are shown in Table 1.

[0062] Example 5

[0063] (1) Preparation of catalyst system

[0064] The same as Example 1, except that the amount of tetrakis(4-formylphenyl)silane used is 2.3 g, and the titanium content of the obtained catalyst component is 2.04 wt%, and the silicon dioxide content is 24 wt%.

[0065] (2) Ethylene slurry polymerization

[0066] Same as Example 1, the polymerization results are shown in Table 1.

[0067] Example 6

[0068] (1) Preparation of catalyst system

[0069] Same as Example 1, except that tetrakis(4-formylphenyl)silane was replaced by tetrakis(4-acetylphenyl)silane in an amount of 2.6 g. The titanium content of the obtained catalyst component was 2.19 wt %, and the silicon dioxide content was 22 wt %.

[0070] (2) Ethylene slurry polymerization

[0071] Same as Example 1, the polymerization results are shown in Table 1.

[0072] Comparative Example 1

[0073] (1) Preparation of catalyst system

[0074] Into a 250mL three-necked flask purged with nitrogen, 2.25g TiC14, 6.0g anhydrous MgCl2 and 150mL tetrahydrofuran were added successively, the temperature was raised to 65°C with stirring, the reaction was carried out at this temperature for 3 hours, and the temperature was lowered to 35°C to obtain a mother liquor.

[0075] Into a 250mL three-necked flask purged with nitrogen, 9g of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1μm) was added, and the cooled mother liquor was added, the temperature was maintained at 35°C, and after stirring for 1 hour, the mother liquor mixed with silica gel was spray dried using a spray dryer. The spraying conditions were: inlet temperature 195°C, outlet temperature 110°C, to obtain a catalyst component with a titanium content of 2.2wt% and a silica content of 25wt%.

[0076] (2) Ethylene slurry polymerization

[0077] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, and 2mL of 1M triethylaluminum / hexane and 0.01g of the above-obtained catalyst system were added at the same time. The temperature was raised to 75°C and hydrogen was added at 0.18Mpa. After hydrogenation, 0.75Mpa of ethylene was added. The temperature was raised to 85°C and the reaction was carried out for 2 hours before the temperature was lowered and the material was discharged. The polymerization results are shown in Table 1.

[0078] Table 1. Catalyst performance obtained in Examples and Comparative Examples

[0079]

[0080] It can be seen from the polymerization data in Table 1 that under the same polymerization conditions, compared with Comparative Example 1, the catalyst containing acylphenyl functional groups of the present invention has higher activity, the obtained polymer has a higher melt index, and the hexane extractable content is lower.

[0081] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. An olefin polymerization catalyst system comprising: An organic aluminum compound and a metal composite component containing acylphenyl groups, wherein the metal composite component containing acylphenyl groups comprises a mixture of tetraacylphenylsilane compounds, magnesium halides, titanium halides, oxygen-containing organic compounds, ultrafine inorganic oxides and / or reaction products of the above components.

2. The olefin polymerization catalyst system according to claim 1, characterized in that In the olefin polymerization catalyst system, the molar ratio of the aluminum element in the organic aluminum compound to the titanium element in the metal composite component containing acylphenyl groups is (5-350):1, preferably (15-180):

1.

3. The olefin polymerization catalyst system according to claim 1, characterized in that The content of titanium in the metal composite component containing acylphenyl groups is 0.2 to 5.0 wt%, preferably 0.8 to 4.0 wt%; and / or, In the metal composite component containing acylphenyl, based on 1 mol of the titanium halide, the amount of the magnesium halide is 0.5-15 mol, preferably 1-10 mol; the amount of the tetraacylphenylsilane compound is 0.02-12 mol, preferably 0.05-8 mol; the amount of the oxygen-containing organic compound is 1-450 mol, preferably 30-250 mol; and / or, In the metal composite component containing acylphenyl groups, the content of ultrafine inorganic oxide is 5 to 45 wt %, preferably 8 to 35 wt %.

4. The olefin polymerization catalyst system according to claim 1, characterized in that The ultrafine inorganic oxide is selected from at least one of alumina and silicon dioxide, preferably silicon dioxide; and / or, The particle size of the ultrafine inorganic oxide is 0.005 to 10 μm, preferably 0.01 to 5 μm.

5. The olefin polymerization catalyst system according to claim 1, characterized in that The general formula of the organoaluminum compound is AlR n X 3-n , wherein R is a C1-C20 straight chain or branched hydrocarbon group, preferably a C1-C10 straight chain or branched hydrocarbon group; X is a halogen, preferably chlorine; 0<n≤3; and / or, The general formula of the tetraacylphenylsilane compound is (R'Ph)4Si, wherein R' is selected from at least one of C1-C8 acyl or alkyl acyl groups, preferably at least one of C1-C3 acyl or alkyl acyl groups; and / or, The magnesium halide is selected from at least one of magnesium chloride, magnesium bromide and magnesium iodide; and / or, The titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide and titanium tetrabromide, preferably at least one of titanium trichloride and titanium tetrachloride; and / or, The oxygen-containing organic compound is selected from at least one of esters, ethers and ketones, preferably at least one of alkyl esters of C1-C8 saturated fatty carboxylic acids, alkyl esters of C7-C8 aromatic carboxylic acids, C2-C8 fatty ethers, C3-C8 cyclic ethers and C3-C10 saturated fatty ketones.

6. The olefin polymerization catalyst system according to claim 5, characterized in that The organoaluminum compound is at least one selected from triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride; and / or, The tetraacylphenylsilane compound is selected from at least one of tetrakis(4-formylphenyl)silane and tetrakis(4-acetylphenyl)silane; and / or, The oxygen-containing organic compound is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, and is preferably selected from at least one of methyl formate, ethyl acetate, n-butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone.

7. A method for preparing the olefin polymerization catalyst system according to any one of claims 1 to 6, comprising: The olefin polymerization catalyst system is obtained by mixing components including the organic aluminum compound and the metal composite component containing acylphenyl groups.

8. The preparation method according to claim 7, characterized in that: The preparation method of the metal composite component containing acylphenyl comprises: (1) reacting components including a tetraacylphenylsilane compound, a magnesium halide, a titanium halide, and an oxygen-containing organic compound to obtain a mother liquor; (2) Adding ultrafine inorganic oxide to the mother liquor obtained in step (1) to obtain a slurry, and spray drying to obtain the catalyst system.

9. The preparation method according to claim 8, characterized in that: In the step (1), the reaction conditions are: the reaction temperature is 60 to 85° C., and / or the reaction time is 2 to 4 hours; and / or, In the step (2), the spray drying conditions include: an inlet temperature of 100 to 240°C, preferably 120 to 200°C; and / or an outlet temperature of 60 to 110°C, preferably 100 to 110°C.

10. Use of the olefin polymerization catalyst system according to any one of claims 1 to 6 or the olefin polymerization catalyst system obtained by the preparation method according to any one of claims 7 to 9 in olefin polymerization reactions.

Citation Information

Patent Citations

  • Polymerization of ethylene catalyst component having high output ratio, preparation and use

    CN101376680A

  • Catalyst for vinyl polymerization and preparation and application thereof

    CN101962417A

  • Alkene polymerization catalyst, preparation thereof and application thereof

    CN102746426A

  • Catalyst component used for olefin polymerization, catalyst, and preparation method of catalyst component

    CN106543316A

  • Siloxane compound-loaded catalyst system as well as preparation method and application thereof

    CN116041571A